Dramat i historia. Z problemów współczesnej dramaturgii rosyjskiej (Heteroglossia – studia kulturoznawczo-filologiczne, 2017)
The article analyses contemporary Russian dramaturgy in the context of socio-political changes taking place in Russia in the 1980s and 1990s of the 20th and the 21st century. The article examines the works of, among others, N. Kolada, N. Sadur, I. Vyrypaev and the Presnyakov Brothers.